Intraovarian platelet-rich plasma injection significantly improves blastocyst yield and quality in IVF patients - Tzu-Ning Yu; Ming-Jer Chen; Tsung-Hsien Lee; Yi-Chun Chen; En-Hui Cheng; Chun-Chia Huang; Chung-I Chen; Chun-I Lee; Maw-Sheng Lee; Pin-Yao Lin (Scientific Reports)
Abstract This study evaluated the effectiveness of intraovarian platelet-rich plasma (PRP) injection in improving ovarian response and embryo quality in IVF patients with poor embryo quality in previous controlled ovarian hyperstimulation (COH) cycles. 74 patients participated, with 30 in the control group and 44 in the PRP group. PRP was injected during the follicular phase for the PRP group. The control group completed two COH cycles, while the PRP group underwent COH cycles before and after the PRP injection. In the first COH cycle, there were no significant differences between groups. However, in the second COH cycle, the PRP group showed significant improvements: the number of fertilized oocytes increased (5.2 ± 3.6 vs. 3.3 ± 3.5, p = 0.011), total blastocysts (1.7 ± 1.5 vs. 0.5 ± 0.7, p < 0.0001) and good quality blastocysts (0.6 ± 0.8 vs. 0 ± 0.2, P < 0.0001). The total blastocyst rate (35 ± 31% vs. 13 ± 24%, p = 0.001) and good quality blastocyst rate (14 ± 22% vs. 1 ± 3%, p < 0.0001) were also higher in the PRP group. The most notable benefits occurred when COH was conducted one to two months post-PRP injection.